CRISPA: A Non-viral, Transient Cas9 Delivery System Based on Reengineered Anthrax Toxin - Hirschenberger, Maximilian; Stadler, Nicole; Fellermann, Maximilian; Sparrer, Konstantin M. J.; Kirchhoff, Frank; Barth, Holger; Papatheodorou, Panagiotis (Frontiers in Pharmacology, 2021)
Translating the CRISPR/Cas9 genome editing technology into clinics is still hampered by rather unspecific, unsafe and/or inconvenient approaches for the delivery of its main components - the Cas9 endonuclease and a guide RNA - into cells. Here, we describe the development of a novel transient and non-viral Cas9 delivery strategy based on the translocation machinery of the Bacillus anthracis anthrax toxin, PA (protective antigen). We show that Cas9 variants fused to the N-terminus of the lethal factor or to a hexahistidine tag are shuttled by pores formed by PA into the cytosol of human cells. As proof-of-principle, we applied our new approach, denoted as CRISPA, to knock out lipolysis-stimulated lipoprotein receptor (LSR) in the human colon cancer cell line HCT116 and green-fluorescent protein (GFP) in human embryonic kidney 293T cells stably expressing GFP. Notably, we confirmed that the transporter PA can be adapted to recognize specific host cell-surface receptor proteins and may be optimized for cell type-selective delivery of Cas9. Altogether, CRISPA provides a novel, transient and non-viral way to deliver Cas9 into specific cells. Thus, this system is an additional step towards safe translation of the CRISPR/Cas9 technology into clinics.